Effect of monomers' structure on self-acid-assisted polycondensation for the synthesis of poly(3, 4-ethylenedioxythiophene) and homopolythiophene. Issue 6 (7th November 2014) - Tusy, Chuong; Jiang, Kang; Peng, Kai; Huang, Lili; Xia, Jiangbin
Abstract : PEDOT and homopolythiophene were synthesized by self-acid-assisted polycondensation (SAAP) based on mono-halogen substituted thiophene derivative monomers. Our results reveal that substituted halogen (bromo or iodo) positions play an important role in SAAP. Abstract : Poly(3, 4-ethylenedioxythiophene) (PEDOT) and thiophene based homopolymers were synthesized by self-acid-assisted polycondensation (SAAP) through mono-halogen substituted thiophene derivative monomers. Detailed characterization of the obtained polymers was carried out by X-ray diffraction (XRD), cyclic voltammetry (CV), infrared spectrum (IR), UV-Vis absorbance spectroscopy, fluorescence spectroscopy (FR) and thermogravimetric analysis (TGA). Most synthesized monomers can be spontaneously polymerized successfully through a simple annealing process at moderate temperature, indicating that they are suitable for SAAP. Moreover, our results reveal that substituted halogen (bromo or iodo) positions play an important role in SAAP, which may pave a wide path for exploring other conjugated polythiophenes through such a facile method.